Extensive exploration of the conformational landscapes of neutral and terminally blocked prolines in the gas phase: A density functional theory study. Issue 4 (July 2022) - Yang, Yizhou; Lin, Zijing
Proline is an important amino acid that plays unique roles in the structures of peptides and proteins. The conformations of proline are searched by a thorough method, generating 3888 trial structures optimized at the B97D/6-311++G** level. A total of 23 conformations are found and their structural and energetic data are presented. All the proline conformers exhibit a coplanar feature for four of the five pyrrolidine ring atoms. The coplanar rule reduces the cost of the conformational search by a factor of 40. The theoretical composition-weighted infrared spectrum provides a good explanation of the experimental results. A conformational search of capped proline yields seven unique conformers, all with trans C-termini peptide planes. The trans C-termini rule further cuts by half the cost of the conformational search of proline-containing peptides. The theoretical composition of the cis N-termini peptide bonds at room temperature is 5.5%, agreeing with the experimental estimations of 3%–10%.